Pengaruh Therapeutic Exercise Walking terhadap Risiko Ulkus Kaki Diabetik pada Klien Diabetes Melitus Tipe 2 di Kelurahan Gebang Kecamatan Patrang Kabupaten Jember (The Effect of Therapeutic Exercise Walking on the Risk of Diabetic Foot Ulcer in Client with Type 2 Diabetes Mellitus at Gebang Village of Patrang District Jember Regency) - Siti Zumrotul Mina; Nur Widayati; Mulia Hakam (Pustaka Kesehatan, 2017)
Diabetes Mellitus is metabolic disease characterized by hyperglycemia. Diabetic foot ulcer is serious complication in diabetic patients which can lead to lower extremity amputation. Therapeutic exercise walking is one of physical activities which can improve blood circulation in the body. This research aimed to analyze the effect of therapeutic exercise walking on the risk of diabetic foot ulcerin patients with type 2 diabetes mellitus. This research employed randomized control group pretest postest design. The sampling technique was simple random sampling involving 15 respondents as intervention group and 15 respondents as control group. Therapeutic exercise walking was done three times a week within a month with the duration of 40 minutes. The data were analyzed using dependent t test and independent t test with significant level of 0.05. The results revealed a significant difference between pretest and postest either in the intervention group (p=0.001) or control group (p=0.048). Furthermore independent t test showed a significant difference between intervention group and control group (p=0.015). This result indicates that there is a significant effect of therapeutic exercise walking on the risk of diabetic foot ulcer. Nurse is expected to apply therapeutic exercise walking to prevent diabetic foot ulcer in diabetes mellitus patients. Keywords: type 2 diabetes mellitus, therapeutic exercise walking, risk of diabetic foot ulcer